Asking Wisdom, Leading the People: Solomon's Example for Transformational Leadership Based on 1 Kings 3:1-15 - Ragil Kristiawan (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2026)
Leadership crises marked by pragmatism and lack of integrity raise the need for a more profound leadership foundation. This study addresses the question: How does Solomon's narrative in 1 Kings 3:1-15 model the four components of transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, and individual consideration) and what underlying theological dimension does it offer? Using a qualitative method with a hermeneutic and exegetical approach, this research conducts an exposition of the text of 1 Kings 3:1-15 followed by an integrative synthesis with transformational leadership theory. The findings reveal that the four pillars of transformational leadership are manifested in Solomon's example: idealized influence through humility and dependence on God, inspirational motivation through a vision of justice and shared welfare, intellectual stimulation by making wisdom a paradigm of thinking, and individual consideration through commitment to justice for the people. Beyond confirming the existing theory, this research identifies a "Transcendental Foundation" as the core that underlies and deepens the four pillars. This foundation is defined as a radical dependence on God manifested through the application of divine wisdom. The result is a transformational theological leadership model where the leader functions as a conduit for divine wisdom. The "Asking Wisdom, Leading the People" paradigm offers a robust spiritual and ethical foundation for leadership, particularly within religious communities.